Design and Application of Prefabricated Basic Components of Additional Elevators in Existing Buildings Based on BIM - Xin Zou (Forest Chemicals Review)
In order to solve the elderly people’s difficulty in getting up and downstairs who are living in multi-storey houses without elevators, our government and related departments are planning to install elevators. However, the traditional method of installing elevators is too expensive and the construction period is too long. This paper focuses on improving the design and the construction technology of the prefabricated basic components of the elevators, by which the influence of the additional elevator structure, on the mechanical properties of the original structure is reduced. The improvement can not only shorten the production cycle, reduce the manufacturing cost, but also meet the requirements for safety without affecting the life of the original residents during the construction because of flexible installation. The shortcomings of the traditional method of installing elevators can be well overcome.